2015
DOI: 10.1002/pc.23647
|View full text |Cite
|
Sign up to set email alerts
|

Water absorption and mechanical properties of PP/HIPS hybrid composites filled with wood flour

Abstract: Water absorption and mechanical performance of the injection‐molded hybrid composites prepared from different ratios of two polymer blends (57 wt%), two compatibilizers (3 wt%), and two wood species (40 wt%) were investigated. The ratio of polypropylene and high‐impact polystyrene (HIPS) gradually increased in the blend (from 10 to 30 wt%). Styrene–ethylene–butylene–styreneblock copolymer and maleic anhydride‐grafted PP (MAPP) were used as compatibilizer (3 wt%). The shore D hardness of the PP/wood composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…Wood-plastic composites (WPCs) possess the combined advantages of wood and plastic; they not only have a natural wood-like appearance, but also have multiple advantages, e.g., they are resistant to degradation, moisture-proof, insect-resistant, higher in dimensional stability, resistant to cracking, not susceptible to warping, etc. WPCs also have good thermoplastics processability, higher hardness than plastic, and could be wearresistant, and aging-resistant (Arnandha et al 2017;Ayrilmis et al 2017;Dias and Alvarez 2017;Wang et al 2017). As an advanced manufacturing technology with the advantages of improving the production efficiency, reducing the cutting force, improving the machining precision and surface quality, and reducing the costs, high-speed cutting technology has been widely used in the cutting of wood-based materials (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wood-plastic composites (WPCs) possess the combined advantages of wood and plastic; they not only have a natural wood-like appearance, but also have multiple advantages, e.g., they are resistant to degradation, moisture-proof, insect-resistant, higher in dimensional stability, resistant to cracking, not susceptible to warping, etc. WPCs also have good thermoplastics processability, higher hardness than plastic, and could be wearresistant, and aging-resistant (Arnandha et al 2017;Ayrilmis et al 2017;Dias and Alvarez 2017;Wang et al 2017). As an advanced manufacturing technology with the advantages of improving the production efficiency, reducing the cutting force, improving the machining precision and surface quality, and reducing the costs, high-speed cutting technology has been widely used in the cutting of wood-based materials (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on the thermal, mechanical, and water absorption properties of WPCs depending on the compositional parameters. 1625 But, melt-state rheological properties of WPCs have been less studied so far compared to their solid-state physical properties. 2630 Kaseem et al.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous swelling over time will eventually lead to micro-cracks in the composites. 2 Even though, there are several articles that reported the research on water absorption of WPCs, [3][4][5][6][7][8][9][10] but with little emphasis on its effects on the tensile and thermal properties. Therefore, realizing its importance in the development of WPCs, this research focuses on studying the effect of water absorption on the tensile and thermal properties of wood fiber-reinforced polymer composite, using mangrove particle (MP) and high-density polyethylene (HDPE) as matrix.…”
Section: Introductionmentioning
confidence: 99%